Proceso de compra de espárrago verde en una empresa agroindustrial de la región La Libertad - Johanson Valdivia, Joel Andre (2015)
Asparagus is a vegetable native to Asia ; cultivation in Peru begins in the early 50 years in the department of La Libertad with the variety Mary , being displaced today mainly by the variety UC157 F1. Extensions planting since 2007 have exceeded 20,000 hectares with a yield of 12200 kg per hectare on average , also the valleys of La Libertad and Ica are those with the highest percentage of asparagus production in Peru. This is due to the favorable conditions in terms of nature, technology and more entrepreneurship , which has allowed the country is the leading exporter of asparagus worldwide. Within this framework Camposol SA , a leading agribusiness is expanding markets and has outlined the strategy to grow annually in the third volume of buying farmers to sustain and have continuity in their efforts to export fresh products , canned and frozen asparagus. Following the principles of continuous improvement sets its purchasing procedure asparagus third stages of exploration , planning, implementation, monitoring and control and feedback as a model of purchase to establish mechanisms to help achieve the objectives of buying asparagus third this year which it is 5000 tons of green asparagus 500 tons of white asparagus . It also makes use of management tools with indicators in each of the stages that lets you measure the performance of this activity and take action forecasting, prevention and corrective as the case of the findings.